1998
DOI: 10.3168/jds.s0022-0302(98)75549-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oral Feeding of Lactobacillus casei Strain Shirota on Immunoglobulin E Production in Mice

Abstract: We investigated the effect of oral feeding of heat-killed Lactobacillus casei strain Shirota on immunoglobulin E (IgE) production in mice. The strain was orally administered to BALB/c mice that had been preinjected intraperitoneally with ovalbumin, and the level of IgE in serum was determined. Results indicated that the oral feeding of L. casei strain Shirota was effective in inhibiting IgE production in serum, and the IgE production in response to ovalbumin was significantly inhibited in the mice. The in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(142 citation statements)
references
References 16 publications
5
136
0
1
Order By: Relevance
“…IL-12 decreases IL-4 production [33]. Accordingly, certain lactobacilli suppress IgE production in vivo and in vitro [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 decreases IL-4 production [33]. Accordingly, certain lactobacilli suppress IgE production in vivo and in vitro [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Some LAB, such as Lactobacillus rhamnosus GG (Goldin et al, 1996), Lactobacillus acidophilus (Goldin and Gorbach, 1977;Lidbeck et al, 1992), Bifidobacterium longum (Reddy and Rivenson, 1993), Lactobacillus casei strain Shirota (Yasutake et al, 2000) and components of LAB (Shiomi et al, 1982) were shown to exert tumor-suppressing effects. For reduction of allergy, Matsuzaki et al (1998) reported that oral feeding of Lactobacillus casei strain Shirota effectively inhibited Immunoglobulin(Ig)E production both in vivo and in vitro. Besides stimulation of antibody production (Alvarez-Olmos and Oberhelman, 2001) and macrophage activity (Schiffrin et al, 1995), functional effects like inhibition of inflammation (Hart et al, 2003;Chapat et al, 2004), and autoimmune disorders (Gill and Guarner, 2004) were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Y-L Ye et al 456 specific lactic acid bacteria (LAB) strain Lactobacillus casei strain Shirota was orally administered 102 or injected 103 together with the particular allergen. In the murine model of birch pollen allergy, Repa et al demonstrated that intranasal co-application of Lactococcus lactis and L. plantarum strains with the recombinant Bet v 1 protein, before and after sensitization with the allergen, resulted in a shift from Th2 to Th1 responses characterized by a marked reduction in the IgE/IgG2a ratio and increased IFN-c production.…”
Section: Strategies Of Mucosal Immunotherapy For Allergic Diseasesmentioning
confidence: 99%